Omni directional loudspeaker using giant magneto striction technology - Loh, Justin Kean Loo (2011)
Audio quality from a surround sound system is always dependent on the placement and configuration of the loudspeaker system. Audio formats such as the Digital Theatre Systems and Dolby Digital sound systems utilize various loudspeaker configurations to form various surround sound effects for listening rooms. Users who are inexperience in setting up a surround sound system will end up in incorrect speaker positions, thus unable to achieve optimal sound output from the system. The purpose of this research is to introduce an alternative loudspeaker system, which only a single speaker is needed for the user to experience a surround sound system regardless of the loudspeaker position. Using a conventional floor standing speaker system to benchmark the directionality of the design, the sound pressure level (SPL) responses of the alternative system at various angles were measured. The results obtained show that the SPL curves of this alternative speaker system are consistent at all angles, with a sensitivity of 77 dB (1W at 1 meter). Conventional loudspeaker system, on the other hand, maintains such values of sensitivity only on-axis listening. With consistent SPL and sensitivity, and omni-directionality, this alternative speaker system has wide listening coverage so that the same listening experience can be achieved regardless of listeners’ position. The proposed loudspeaker system has been able to simplify the setup and to locate the correct loudspeaker placement.